SPEECH ACTS BY KARNI ILYAS IN INDONESIA LAWYERS CLUB (ILC) ‘KPK VS NOVANTO: BERPACU DENGAN WAKTU - Theresia Fransiska Sidabutar; Zainuddin - -; Busmin - Gurning (LINGUISTIK TERAPAN, 2020)
This research deals with the using of speech acts in Indonesia Lawyers Club (ILC): KPK vs Novanto: Berpacu dengan Waktu. The objectives of this research were: (1) to investigate the types of speech acts used by Karni Ilyas in ILC “KPK vs Novanto: Berpacu dengan Waktu”, (2) to describe the way of performing speech acts realized by Karni Ilyas, and (3) to explain the reasons why those types of speech acts are realized by Karni Ilyas. The research applied descriptive qualitative method. The source of data in this research was taken from Indonesia Lawyers Club (ILC) “KPK vs Novanto: Berpacu dengan Waktu” video. The instrument used for collecting the data was the observation by recorded the utterances of Karni from seven parts of videos. The data were clauses contained of Speech Acts used by Karni. The findings of this study showed that: 1) There were three types of speech acts, namely locutionary act, illocutinary act and perlocutionary act that utilized by Karni Ilyas in his utterances when discussion with all the guests in Indonesia Lawyers Club (ILC) “KPK vs Novanto: Berpacu dengan Waktu”. The dominant types of speech act was illocutionary act and the dominant classification was directive. 2) There were two ways in performing speech act used by Karni, namely direct and indirect speech. Direct speech was more dominant than indirect speech. 3) There were four reasons why Karni using speech act, namely to actuate, to entertain, to stimulate, and to inform. The dominant was to actuate. Keywords: Speech Acts, Karni Ilyas, Indonesia Lawyers Club